PENGARUH KONFLIK KERJA, KARAKTERISTIK INDIVIDU DAN DISIPLIN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI DI BADAN PENANGGULANGAN BENCANA DAERAH PROVINSI SUMATERA UTARA - Fahruddin .; Lisman Saragih; Rajid Yuliawan; Rahmalinda .; Ismail Nasution (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The effectiveness of work needs to be considered because it has a great effect on the interests of the organization. Effectiveness means that a pre-planned goal can be achieved or in other words the goal achieved due to the activity process. Effectiveness can also be viewed so that the implementation of administration more achieves the results as planned, achieves the goals to be achieved and more successfully useful or appropriate. The purpose of this study was to find out the influence of work conflicts, individual characteristics, and work disciplines on the effectiveness of employee work in the Regional Disaster Management Agency of North Sumatra Province. This study uses an associative approach, which is research conducted to find out the influence or relationship between free variables and bound variables. The results showed that partial work conflicts had a significant influence on the effectiveness of employee work. Partially, individual characteristics have a significant influence on the effectiveness of employee work. Partially discipline has a significant influence on the effectiveness of employee work. Simultaneously the influence of work conflicts, individual characteristics, and work disciplines has a significant influence on the effectiveness of employee work.